Evaluating the impact of maternal vitamin D supplementation: I. Sow performance, serum vitamin metabolites, and neonatal muscle characteristics - Flohr, Joshua R.; Woodworth, Jason C.; Bergstrom, J. R.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M. (My University, 2017)
In Exp. 1, 56 gestating sows (PIC 1050; 35 d postinsemination) were used in a 30-d trial to determine serum 25(OH)D-3 response to increasing concentrations of dietary vitamin D3. Sows were randomly allotted to 1 of 7 dietary D3 treatments (200, 800, 1,600, 3,200, 6,400, 12,800, or 25,600 IU of added D3 per kilogram of complete diet) with 8 sows per treatment. Increasing D-3 increased (quadratic; P < 0.001) serum 25(OH)D-3 with the response depicted by the prediction equation: serum 25(OH) D3, ng/mL = 35.1746 + (0.002353 x dietary D-3, IU/d)- (0.0000000156 x dietary D3, IU/d(2)). In Exp. 2, 112 sows and their litters were used to determine the effects of dietary vitamin D regimen on sow performance, subsequent preweaning pig performance, neonatal bone and muscle characteristics, and serum vitamin metabolites. Sows were allotted to 1 of 4 dietary treatments 3 to 5 d following breeding: 800, 2,000, or 9,600 IU of D-3 per kilogram of the diet or 50 mu g of 25(OH) D-3 (2,000 IU of D-3 equivalent from Hy- D, DSM Nutritional Products, Parsippany, NJ) per kilogram of diet. There were 25 to 27 sows per treatment. Increasing dietary D-3 increased (linear, P = 0.001) serum 25(OH) D-3 of sows on d 100 of gestation, at farrowing, and at weaning. Increasing D-3 in sow diets increased piglet serum 25(OH)D-3 at birth (linear, P = 0.001) and weaning (quadratic, P = 0.033). Sows fed 50 mu g of 25(OH)D-3/kg had intermediate (P < 0.004) serum 25(OH)D-3 concentrations on d 100 of gestation, at farrowing, and at weaning compared with sows fed 2,000 IU of D-3/kg and sows fed 9,600 IU of D3/kg. Pigs from sows fed 50 mu g of 25(OH) D3/ kg had greater serum 25(OH)D-3 compared with pigs from sows fed 2,000 IU of D-3/kg, but at weaning, serum 25(OH)D-3 concentrations were similar. Also, pigs from sows fed 9,600 IU of D-3/kg had greater (P = 0.011) serum 25(OH) D3 at birth and weaning compared with pigs from sows fed 50 mu g of 25(OH) D-3/kg. Maternal performance, litter characteristics, neonatal bone ash content, and neonatal muscle fiber characteristics were largely unaffected by the dietary vitamin D treatments. Overall, D3 and 25(OH) D3 are both useful at increasing serum 25(OH)D-3 concentrations, but more D3 (on an equivalent IU basis) is needed to achieve similar serum 25(OH)D-3 responses compared with feeding 25(OH)D-3. Concentration of maternal vitamin D supplementation in lactation impacted milk transfer of the vitamin more so than the form of the vitamin, as evidence by the weaned pig serum 25(OH)D-3 concentrations.
Citation: Flohr, J. R., Woodworth, J. C., Bergstrom, J. R., Tokach, M. D., Dritz, S. S., Goodband, R. D., & DeRouchey, J. M. (2016). Evaluating the impact of maternal vitamin D supplementation: I. Sow performance, serum vitamin metabolites, and neonatal muscle characteristics. Journal of Animal Science, 94(11), 4629-4642. doi:10.2527/jas2016-0409
Keywords: 25(Oh)D-3; Sow Nutrition; Vitamin D; Muscle Characteristics; Skeletal-Muscle; Reproductive-Performance